Carbon-neutral blueprint strategies and challenges - Dr Muhammad Radzi, Abu Hassan; Huszian, Husin; Noor Muhammad, Abd Rahman; Khairul Azmy, Kamaluddin; Muhammad Syukri Imran, Abdullah (Step Communications Ltd, 2025)
The Malaysian Carbon Neutral Healthcare Facilities Blueprint outlines the roadmap for achieving carbon neutrality in healthcare facilities across Malaysia, and delineates key strategies aimed at reducing carbon emissions and promoting sustainability within the healthcare sector. Several challenges hinder the implementation of these strategies, including financial constraints, technological limitations, and regulatory frameworks. Overcoming these is crucial to realising the vision of carbon-neutral facilities in Malaysia and advancing towards a more sustainable healthcare system, as Dr Muhammad Radzi bin Abu Hassan, Ts Huszian Husin, Dr Noor Muhammad Abd Rahman, Dr Khairul Azmy Kamaluddin and Dr Muhammad Syukri Imran Abdullah explain